Statin and cyclooxygenase‐2 inhibitors improve survival in newly diagnosed diffuse large B‐cell lymphoma: a large population‐based study of 4913 subjects. (17th April 2020) - Smyth, Liam; Blunt, Danielle N.; Gatov, Evgenia; Nagamuthu, Chenthila; Croxford, Ruth; Mozessohn, Lee; Cheung, Matthew C.
Summary: Preclinical data suggests anti‐lymphoma potential for statins, metformin and cyclooxygenase‐2 (COX‐2) inhibitors. We performed a retrospective population‐based study of all adults aged ≥66 years diagnosed with diffuse large B‐cell lymphoma (DLBCL) or transformed lymphoma treated with a rituximab containing regimen, between 2005 and 2015 in Ontario, Canada. Using administrative databases, we assessed the impact of medication exposures, prior to chemo‐immunotherapy, on lymphoma survival. Cox regression analyses, controlling for sociodemographic factors and comorbidities, examined the relationship between medication exposure and survival. In total, 4913 patients were treated with curative intent (median age 75 years, 51% male) and 52·2% died at a median of 1 year from treatment initiation (67% due to DLBCL). In the year prior to commencing treatment, 45·7% received statins, 16·3% metformin, and 25·0% a COX‐2 inhibitor. Adjusting for confounders, exposure to statin and COX‐2 inhibitors prior to chemo‐immunotherapy independently conferred a survival advantage: statin exposure for 30 days (hazard ratio [HR] 0·97, 95% confidence interval [CI] 0·96–0·98), 180 days (HR 0·84, 95% CI 0·80–0·89) and 365 days (HR 0·71, 95% CI 0·63–0·79) and COX‐2 inhibitor exposure for 30 days (HR 0·95, 95% CI 0·95–0·98), 180 days (HR 0·76, 95% CI 0·66–0·86) and 365 days (HR 0·57, 95% CI 0·43–0·74). Metformin had no significant impact. This population‐based study found a dose‐related survival benefit of exposure to statins and COX‐2 inhibitors prior to chemo‐immunotherapy for newly diagnosed DLBCL.